Risiko Usaha Peternakan Ayam Broiler di Kecamatan Kapuas Kabupaten Sanggau (Jurnal Agribisnis Indonesia, 2024)
One of the agricultural subsectors that has the potential to be developed is the livestock subsector. The livestock sector has great potential with the increase in chicken meat consumption every year but has complex problems from both internal and external factors, giving rise to risks and uncertainty. Therefore, there is a need for further research aimed at identifying sources of risk, analyzing the magnitude of production and price risks in partnered and non-partnered broiler chicken farming businesses so that risk management can be identified that can be applied to control risks in broiler chicken businesses in Sanggau Regency. The method used in this research is the method of observation and direct interviews with business owners and collecting data in the form of questionnaires with a combined research approach, namely a method that combines quantitative methods and qualitative methods in research so that more comprehensive, valid, reliable and objective data is obtained. The results of research conducted in Kapuas District, Sanggau Regency show that the risks faced by farmers are social risks in the form of lawsuits and theft, physical risks in the form of fires caused by negligence, production risks originating from DOC quality factors, weather, disease, human resources, predators, cage conditions, food and drink, fluctuations in selling prices, high input prices. The high risk of broiler chicken farming can also be seen from the coefficient of variation value ≥ 0.5, which indicates that the broiler chicken farming business faces the possibility of making a loss in each period.